Laser-Induced Graphitization of Polyimide Tape as Modifiable Sensor in Anodic Stripping Voltammetry - Laura Chirivì; Antonio Serra; Antonio Della Torre; Riccardo Di Corato; Rosaria Rinaldi; Alessandra Aloisi (Proceedings)
The monitoring of toxic contaminant traces in the environment needs a simple and sensitive method, such as stripping analysis that applies a pre-concentration step to the analyte on the working electrode. The present work focuses on the realization of a two-electrode sensor made by means of laser-induced graphitization of a polyimide (PI) tape. Moreover, taking advantage of the strong affinity of Bi for metal ions for detection by Anodic Stripping Voltammetry (ASV), the proposed sensor implementation involved the use of Bi2O3 nanopowder as the precursor of Bi film as eco-friendly Hg substitute. Physicochemical analyses were conducted to investigate elemental and structural differences in relation to the shifts recorded in the voltametric behavior.